CT SCAN EXAMINATION TECHNIQUE OF THE HEAD WITH CLINICAL SUSPECT OF HEMORRHAGIC STROKE IN THE AULIA HOSPITAL RADIOLOGY INSTALLATION - Salwa Innasya Sugesty; Anisya Fitri (Medical Imaging and Radiation Protection Research Journal, 2024)
Hemorrhagic stroke is a cerebrovascular condition caused by the rupture of a blood vessel in the brain, resulting in bleeding and impaired neurological function. A CT scan of the head is one of the main modalities in evaluating stroke because it can provide an image of the brain structure and detect bleeding quickly. One of the technical parameters that plays a role in producing CT scan image quality is slice thickness. Differences in slice thickness can affect the level of anatomical detail and the ability to visualize pathological abnormalities. This study aims to determine the technique of CT scan of the head in patients with clinical suspicion of hemorrhagic stroke and the use of slice thickness in the Radiology Installation of Aulia Hospital. This study used a qualitative method with a case study approach. Data collection was carried out through observation, interviews, and documentation involving two radiographers and one radiologist. The results showed that the CT scan of the head was performed without special preparation, with the patient positioned supine, head-first, and object settings based on the Mid Sagittal Plane (MSP) and Mid Coronal Plane (MCP). The examination used a slice thickness parameter of 1 mm with a scanning time of 60 seconds, a FOV of 200 mm, a voltage of 130 kV, and a current of 25 mA. A 1 mm slice thickness was used to obtain more detailed images. The use of thin slices can increase image detail, helping to more clearly demonstrate structures and pathological abnormalities. This study demonstrates that the implementation of the 1 mm slice thickness head CT scan protocol at Aulia Hospital differs from some literature that uses a larger slice thickness.